AICCRA leveraging on networks to communicate climate information and climate smart agriculture to smallholder farmers in Zambia - Homann-Kee Tui, Sabine; Wilkinson, Melanie; Moyo, Martin; Ngwira, Amos R; Poulos, Allison; Schuetz, Tonya; Gbegbelegbe, Sika; Pele, Winnie; Jacobs-Mata, Inga (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
AICCRA Zambia supports networks and community responses through programs on climate innovation and agribusiness, leveraging on media and communication channels. Interventions are designed to stimulate networks of actors at multiple levels (macro, meso, micro) that catalyse dissemination of climate information and climate smart products and services to smallholder farmers. At project level, communication and outreach strategies that support networks and linkages within and across the networks can also contribute to achieving impact. Network strengthening and media communications can provide an important bridge for research, development, climate and agri-business to achieve their targets of enhancing uptake of climate information and climate smart agriculture. Assessment tools are being developed to identify what networks, partnerships and strategic stakeholders the media can leverage on and start working with. Assessing value creation stories with key stakeholders will show how communication and outreach activities of the AICCRA project have resulted in stimulating response by intermediaries and end-users and improved program performance and impact on smallholder farmers. Providing feedback on how good the media interventions were, how they contributed to local impact pathways, and what new opportunities for partnerships were discovered, supports monitoring and evidencing achievements in accordance with the project results framework.